Selection Of Promising Broccoli Varieties Suitable For The Conditions Of Southern Uzbekistan (Texas Journal of Agriculture and Biological Sciences, 2025)
The article presents the results of studies conducted to select promising varieties of broccoli suitable for the conditions of southern Uzbekistan. Promising samples are identified by the duration of the fruiting period and overall yield.